"Let's Not Talk about It:" Multiple Perspectives on Service Barriers and Recommendations for Black Sexual Assault Survivors: A Mixed-Methods Study. Issue 47 (2nd January 2021) - Sualp, Kenan; Forgetta, Shayna; Anderson, Kim; Revell, JoEllen; Godbee, Brandi
Abstract: This study employed a mixed-methods design to examine victim service barriers on local and state levels for Black/African-American (AA) sexual assault (SA) survivors. Victim-serving organizations (VO, n = 22) across a state-wide SA coalition were surveyed along with non-victim organizations (NVO, n = 26) that serve Black/AA clients/individuals (e.g., public service agencies/churches) in a local urban area. Survey findings highlight the most critical barrier was fear and mistrust of the legal system. Other significant barriers included: fear of perpetrator retaliation, cultural disclosure norms, lack of service awareness and transportation, mismatch between survivor-provider demographic characteristics, and survivor shame/stigma. In addition, a focus group (n = 8) of Black/AA SA survivors, VOs, and NVOs was conducted in response to the survey findings. Thematic analysis indicated a multi-system approach across individual, organizational, and system levels was necessary to effectively impact barriers and improve access for Black/AA SA survivors. Lessons learned include the importance of cultural context and relevance in offering organizational services for victimized marginalized populations. Such knowledge may be translated into prevention and intervention efforts to improve services. Recommendations for future inquiry include replicating this study by using larger sample sizes that include Black/AA SA survivors and evaluating the effectiveness of the recommendations offered in this study.